Managing Academics During COVID-19 - Shaik, Ramjan (Indian Journal of Pharmacy Practice)
In December 2019, an outbreak of pneumonia of unknown origin was reported in Wuhan, Hubei Province, China. The disease is called coronavirus disease 2019 (COVID-19). When an infected person sneezes or coughs, sending tiny droplets into the air, people can catch coronavirus. People also can get infected if they touch an infected droplet on a surface and then touch their own nose, mouth, or eyes. The transmission rate is relatively high and the virus can lead to pneumonia, respiratory failure, septic shock, and death.